Credit Risk Management At Private Banks Operating In Syria Through The Resolution No. 597 Of Money And Credit Council - Hassani, Abdul Razzak; Bayoud, Marwa (Latakia University Journal - Economic and Legal Sciences Series, 2020)
This paper aims to examine credit risk, for a sample of private banks during recent Syrian crisis, Through the application of Money and Credit Council Resolution No. 597 of 2009 related to debt classification and credit risk management. Also it is testing if there are differences between the studied banks in applying this resolution and to evaluate credit polices. The analytical descriptive approach was followed in the research, the Author concluded that the banks in question differed in applying the resolution No.597; that Bank of Jordan and Bank Audi are respecting the resolution by following councils credit policy. While Al Baraka Bank and Islamic World Bank both of them depends on the provision of direct credit facilities, and follows a non-performing financing policy that leads to higher non-performing loans resulting from the granting of these facilities. يتناول هذا البحث دراسة إدارة المخاطر الائتمانية لعينة من المصارف الخاصة في ظل الأزمة الراهنة، وذلك على ضوء قرار مجلس النقد والتسليف رقم 597 لعام 2009 المتعلّق بتصنيف الديون وإدارة مخاطر الائتمان. وهدف البحث إلى دراسة الفروق بين المصارف المدروسة في تطبيق هذا القرار؛ وتقييم السياسة التمويلية التي تتبعها المصارف المدروسة. وقد توصلت الباحثة إلى أنّ هناك تباين فيما بين المصارف في تطبيق القرار (597)؛ حيث يتّبع كل من بنك الأردن، وبنك عودة سياسة تمويلية حذرة. وأنّ بنك البركة والبنك الدولي الإسلامي كل منهما لا يتبع سياسة حذرة تماماً حيث يقومان بتقديم التسهيلات الائتمانية غير المباشرة بدرجة أكبر من باقي المصارف عيّنة الدراسة، الأمر الذي انعكس بارتفاع الديون غير المنتجة الناتجة عن منح هذه التسهيلات.